2020
DOI: 10.13057/biodiv/d211163
|View full text |Cite
|
Sign up to set email alerts
|

Impact of highway on vertebrate roadkill in Nam Nao National Park, Thailand

Abstract: Abstract. Kummoo W, Teampanpong J, Paansri P, Suksavate W, Utsa P, Duengkae P, Prompat S. 2020. Impact of highway on vertebrate roadkill in Nam Nao National Park, Thailand. Biodiversitas 21: 5540-5550. Roads lead to biodiversity loss, primarily through wildlife collisions. This phenomenon is widespread, despite limited attention in Thailand. To reduce road mortality, the roadkilled species and their distributions along the road become a significant component for designing management strategies. We surveyed ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
1
2
0
Order By: Relevance
“…They can be seen catching small animals that stand on the road so it's possible that when a snake or other reptile dies by car collision, these birds of prey take them away, probably causing a lack of data for this group. Scavenging and carcass removal as been reported by other authors as Zhang and collaborators (2018) or Kummoo et al (2020). The only snake present in the study was possibly registered due the particularity of the location.…”
Section: Discussionsupporting
confidence: 78%
“…They can be seen catching small animals that stand on the road so it's possible that when a snake or other reptile dies by car collision, these birds of prey take them away, probably causing a lack of data for this group. Scavenging and carcass removal as been reported by other authors as Zhang and collaborators (2018) or Kummoo et al (2020). The only snake present in the study was possibly registered due the particularity of the location.…”
Section: Discussionsupporting
confidence: 78%
“…304 that pass through KYNP and Thap Lan National Park on the wildlife between December 2018 and August 2019 with a total accumulative distance of 1062 km found 41 wildlife carcass species, with 176 individuals were killed that showed 0.17 WVCs km -1 . Kummoo et al (2020) reported the WVCs on the highway that cuts through Nam Nao National Park, Thailand. Based on a 1496 km survey, they reported 1389 carcasses of 578 amphibians, 540 reptiles, 190 mammals, and 81 birds, which accounted for 1389 carcasses or 0.93 WVCs km -1 .…”
Section: Discussionmentioning
confidence: 99%
“…Roadkilled O. porphyraceus have been reported from Hong Kong, Thailand, and Taiwan (Karsen et al 1998;Kummoo 2020;Lin 2022). Roads dissecting natural habitats force animals to cross these hazardous artificial linear structures to search for mates and to locate critical resources (Smith 2003).…”
Section: O N S E R V At I O N a N D N At U R A L H I S T O R Ymentioning
confidence: 99%